Rancang Bangun dan Analisis Opening Bumper Program TV dalam bentuk Motion Graphic (Studi Kasus: Bincang Santai di iNews TV Batam) - Evaliata Br Sembiring; Jonathan Elsson Suhendra; Prasetyo Dharsono; Fadil Mayuheru (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
Opening Bumper is a short animation opening video in a program that describes the identity of an event or agency. One of the TV programs was "Bincang Santai" which airs on the local television station, iNews Batam. However, the opening bumper of the “Bincang Santai” program has been showing for more than 4 years, which doesn’t represent the identity of the current “Bincang Santai” program. Therefore, a new opening bumper was made in motion graphic form. In making the opening bumper, the Sherwood-Rout method was used. Furthermore, analysis of the feasibility as an opening bumper and the perception of the public through the EPIC Model approach. The results of the research are: (1) The resulting opening bumper has a duration of 18 seconds in .mpg format. The opening bumper contains a brief snippet of the “Bincang Santai” TV program with various motion graphic elements; (2) Opening bumper as the “Bincang Santai” opening bumper is considered feasible based on indicators: typography, color, visual effects, objects, and music, which reaches a score of 4.22; (3) The opening bumper is considered effective in conveying the identity of the “Bincang Santai” TV program in brief, based on the average EPIC dimension achievement of 4.59.